DOLO OR GUILT IN RESPONSIBILITY FOR BAD PRAXIS OF HEALTH PROFESSIONALS - Rene Raul Deza Colque (2019)
In the present investigation we present some criteria to determine the criminal responsibility of health professionals (doctors) in their various interventions of their medical practice. With what we do not intend to leave the problem exhausted because it is a reality that today has become viral. We have as an objective that law operators have better possibilities of applying the theories provided by criminal law, in order to determine if it constitutes eventual misconduct or conscientious guilt, when protected by legal malpractice, protected legal assets such as life or people's health. To this end, the different doctrinal criteria they have developed in relation to fraud and guilt have been reviewed, in addition to taking into account the jurisprudence that has so far been issued by the Judiciary. It has been determined that if the health professional is aware that with his behavior he increases the risk, this is sustained in specific circumstances, such as not having adequate infrastructure conditions, implementations of medical equipment for the possible care of any emergency, not having ambulance, not having adequate care personnel, be aware that the place where you perform a surgical intervention does not have authorization from the Ministry of Health, and the corresponding Municipality, acts with the element of knowledge required by the eventual intent. Likewise, the volitional element of the eventual intent is represented by a decision taken by the health professional, to continue with the surgical intervention in these conditions.